2020
DOI: 10.1111/dth.13307
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of subclinical atherosclerosis in Turkish patients with acne vulgaris receiving systemic isotretinoin

Abstract: Studies conducted on isotretinoin have shown that it may indirectly lead to atherosclerosis. The objective of this study was to determine the effect of systemic isotretinoin on subclinical atherosclerosis. The present study included 63 patients with acne vulgaris who had used isotretinoin for 6 months. Glucose, insulin, and homeostatic model assessment of insulin resistance levels; body mass index; waist circumference; blood pressure; lipid profile; and lectin‐like oxidized low‐density lipoprotein receptor‐1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…Saklamaz et al reported that CIMT increases after 4 months in acne patients receiving ISO treatment, so they have suggested that long‐term ISO use increased atherosclerosis risk 7 . In another study, it was claimed that ISO triggered the development of subclinical atherosclerosis in men 25 . In the light of all these data and the findings of our study, we can explain the atherosclerosis pathway seen in Figure 1.…”
Section: Discussionsupporting
confidence: 82%
“…Saklamaz et al reported that CIMT increases after 4 months in acne patients receiving ISO treatment, so they have suggested that long‐term ISO use increased atherosclerosis risk 7 . In another study, it was claimed that ISO triggered the development of subclinical atherosclerosis in men 25 . In the light of all these data and the findings of our study, we can explain the atherosclerosis pathway seen in Figure 1.…”
Section: Discussionsupporting
confidence: 82%
“…9 In another study, it was claimed that ISO triggered the development of subclinical atherosclerosis in men. 29 In the light of all these data and the findings of our study, we can explain the atherosclerosis pathway seen in Figure 1. It was thought that the ISO-induced uric acid increase might be related to dyslipidemia.…”
Section: Discussionsupporting
confidence: 63%
“…A total of 16 studies qualified for assessment of eligibility. Finally, 1 study [ 17 ] was excluded according to the exclusion criteria, while 15 studies [ 6 , 7 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] were found eligible for qualitative and quantitative analysis, including 380 acne vulgaris patients under systemic isotretinoin.…”
Section: Resultsmentioning
confidence: 99%